The EFL Students’ Perceptions on the Use of Genshin Impact in Increasing Reading Skills - Arfani, Sabiq Ahsan; Nita Kaniadewi (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The rise of game-based learning in English language teaching signifies a shift towards more engaging and interactive methods. Genshin Impact is a game that can be used as an alternative media to improve students' English skills, specifically reading, through its interactive gameplay. The game's requirement to understand characters' dialogues is valuable for developing reading skills. This research investigates whether games, particularly Genshin Impact, can enhance students' reading skills by assessing how much this game positively impacts students' reading abilities. The qualitative method is used with interviews as the instrument in data collection to ensure a more in-depth understanding of the obtained data. The research was conducted on ten UHAMKA students from various departments and semesters. Of the ten students who participated in the study, most saw Genshin Impact as a language learning tool that enhanced their English language skills with a focus on reading. However, not all respondents reported reading improvements. However, as participants played more Genshin Impact, there was a positive correlation between increased playtime and the levels of improvement in English language skills of the participants. Participants learned further aspects of English, vocabulary development, contextual understanding, and reading proficiency by playing Genshin Impact.